Factors affecting complications of transrectal ultrasound-guided prostate biopsy: A cohort study with 403 patients in a single center - Kölükçü, Engin; Beyhan, Murat; Atılgan, Doğan (Journal of Surgery and Medicine, 2019)
Aim: Prostate cancer is among the common cancer types in male population. Transrectal ultrasound (TRUS) guided prostate biopsy is considered the gold standard for diagnosis of prostate cancer. Complications in this tissue sampling method were analyzed in the present study. Methods: A descriptive study with retrospective design was planned. A total of 403 patients who had 12 core TRUS guided prostate biopsy for the first time in December 2016 -November 2018 period were evaluated. Age of the patients, digital rectal examination finding, prostate specific antigen (PSA) levels, prostate volumes and complications were analyzed. Results: Average age, serum total PSA level and prostate volume of patients were 63.2±8.53 years, 21.6±18.19 ng/mL and 65.63±20.19 cc, respectively. Genitourinary system infection was observed in 7.2% of the patients after the procedure. In terms of non-infection complications, 23.1% of patients had hematuria, 16.1% hematospermia and 2.2% rectal bleeding. On the other hand, 4.2% of the patients had vasovagal episodes and 0.7% had acute urinary retention. Of all patients, 8.9% were hospitalized due to observed complications. Conclusion: We conclude that TRUS-guided prostate biopsy is a reliable diagnostic tool with low complication rates in patients with prostate cancer pre-diagnosis.